The great pretender returns to Dublin, Ireland. Issue 5 (1st October 2001) - Hopkins, S; Lyons, F; Mulcahy, F; Bergin, C
Abstract : Background: An outbreak of syphilis has been identified primarily in Dublin, Ireland. On a background of a stable low incidence of syphilis, a significant increase in the number of cases of syphilis has been observed over the past 18 months. Results: 181 cases of syphilis were seen in this period. 121 were defined as early syphilis. These cases were mainly among men who have sex with men (92%). A high rate of HIV co-infection was present; 16 patients who regularly attended HIV clinics were diagnosed with early syphilis. Nine patients were co-diagnosed with HIV and early syphilis. High risk behaviour and concurrent diagnoses with other sexually transmitted infections were prevalent in this cohort. Sexual networks were also investigated. Conclusion: An education campaign, widespread advertisements, and on-site testing in commercial venues have revealed further cases. Safer sex messages need to be emphasised particularly among the HIV population. Further innovative strategies continue to be explored.